Sustainability Reporting and SWOT Analysis: Case Study PT Asuransi Sinar Mas - Saputra, Pandu Perdana; Wulaningsih, Ririn Widyastuti; Mais, Rimi Gusliana; Oktasari, Erita (Research of Finance and Banking, 2024)
This study aims to analyze the strengths and weaknesses of PT Asuransi Sinar Mas, along with external factors such as opportunities and threats, through a SWOT analysis of the company's 2023 sustainability report. PT Asuransi Sinar Mas, one of Indonesia's largest insurance companies, is an ideal research subject to evaluate how major players in the insurance industry navigate challenges and leverage opportunities to achieve long-term sustainability. A qualitative approach, using literature reviews and case study analysis, was employed. The results indicate that the company has significant potential for growth if it can capitalize on its strengths and opportunities while addressing weaknesses and managing threats effectively. The managerial implications suggest that sustainability reporting and thorough analysis provide critical insights for effective organizational management. Transparent reporting helps managers make informed decisions, build stakeholder trust, and foster innovation, ultimately supporting long-term business sustainability.